RESPON WISATAWAN TERHADAP PENGEMBANGAN BATUR GLOBAL GEOPARK BALI - Gian Saputra, I Gede (Jurnal Master Pariwisata (JUMPA); Volume 02, Nomor 02, Januari 2016DO - 10.24843/JUMPA.2016.v02.i02.p05)
Batur Global Geopark is one of the new tourism attractions being developed by the government in Kintamani, Bali. This new attraction has not contributed significant impacts to the number of tourists visiting Kintamani. Lack of site managemenet and promotion are among the causes. This study analyzes the response of tourists towards the development of Batur Global Geopark based on attitudes, perceptions, and participation. Data collected by observation, in-depth interviews, surveys, and analyzed using Likert scale by giving score against to the response. The study shows that the development of Kintamani geopark is expected to be one of the tourism products which could provide a new attraction for tourist to come to Kintamani. Accordingly, the government needs more in-depth introduction of Batur Global Geopark by creating special tour itinerary to attaind the purpose of conservation, education, and geotourism.
Keywords: tourists response,Batur Global Geopark, development, Kintamani